Manhaj Ithbat Salaf Scholars in Interacting with Characteristics of Khabariyyah According To The Explanation Of Imam Abu Al-Hasan Al-Ash`Ari - Mohd Saiba Yaacob; Syed Hadzrullathfi Syed Omar; Engku Ibrahim Engku Wok Zin (Rabbanica: Journal of Revealed Knowledge)
The works in the field of belief produced by Imam Abu al-Hasan al-Ash`ari (Imam al-Ash`ari) have been used as an essential reference by Islamic scholars to understand the exact method of interacting with Sifat Khabariyyah. Referring specifically to the book of al-Ibanah and Maqalat al-Islamiyyin, Imam al-Ash`ari explained that Ithbat is a method that has been adopted by the Companions RA, Tabi`in and Ahl al-Hadith. The problem that arises is that Islamic scholars have different opinions when discussing the concept of Ithbat according to the perspective of Salaf scholars, whether they have the concept of Tafwid al-Kayfiyyah or the concept of al-Ithbat bi La Kayf. Therefore, this study aims to discuss the concept of Ithbat and the characteristics of the method of Ithbat of Salaf scholars according to the explanation of Imam al-Ash`ari. Using a document analysis approach, a literature review was used to conduct a qualitative study. The findings indicated that the Salaf scholars' Ithbat method is based on the concept of al-Ithbat bi La Kayf, which is explained by Imam al-Ash`ari. One of its main features is that it teaches the Sifat Khabariyyah's external meaning as worthy of Allah SWT by rejecting the existence of kayfiyyat (form, appearance, characteristics, and manner), without interpretation, without ta'wil (representation), without tamthil (equalisation), without tashbih (simulation), and denying the Sifat al-huduth (new attributes) like location, mass, movement, and displacement. All at once, the findings of this study challenge the validity of the Tafwid al-Kayfiyyah method, which establishes the existence of certain kayfiyyat for the Dhat and Nature of Allah SWT and refuses to deny the new attributes.